Structure of Corporate Governance Important to Reduce Manipulation of Financial Statement: The Empirical Studies in the Indonesia Context - Ardi Paminto, Yana Ulfah, Muhammad Ikbal, Irwansyah Irwansyah, Dio Caisar Darma (International Journal of Advanced Science and Technology, 2020)
The structure of corporate governance in Indonesia is rather different than the other countries, especially the structure of the supervisory board, but in general, it has still similarities. How important is the corporate governance structure to reduce the manipulation of a financial statement? This question is a fundamental question of this research. The current rumors which are spreading, fraudulent financial statements are massively happened, not only in Indonesia but also in many countries around the world which experience the same problem. Our study aimed to analyze the structure of corporate governance towards financial statement manipulation. We used sample data of manufacturing companies in 2016. We used logistic regression to test hypotheses which explain the impact of fraud on corporate governance. The researcher used the Beneish Ratio Index which is introduced by Beneish (1999) to detect fraudulently on financial statements. In general, our findings supported the hypothesis, except for three hypotheses which test three variables, namely the concentration of ownership, the independent commissioner portion and the use of big four Accounting Firm. Our findings show that the Indonesian audit environment especially auditor has low motivation to provide high-quality audits.